Impact on Dividend Payout Analysis between Nepal Bank Limited, Rastriya Banijya Bank Limited and Agricultural Development Bank Limited - Aryal, Rameshower (Journal of Kathmandu BernHardt College, 2022)
This study entitles, “Factors Analysis on Dividend Payout of Nepal Bank Limited, Rastriya Banijya Bank Limited and Agricultural Development Bank Limited” focused on quantities paid are decided on the company's performance analysis of Nepal Bank Limited (NBL), Rastriya Banijya Bank Limited (RBB) and Agricultural Development Bank Limited (ADB) taking three sample banks. This study focused to find the effects of different factors and on its dividend payout taking secondary data from 2012/13 to 2021/22. The study’s finding indicate that larger corporations may afford to pay bigger dividends because of their greater financial strength. Also the profitability ratio, company size, and leverage ratio all have a negative correlation with the dividend payout ratio and as the bank's size grows, the dividend distribution will be reduced and increases in net income have a positive impact on dividend payments, meaning that higher payments will be made when growth is strong.